“Elaboración del manual de buenas prácticas de manufactura en el camal municipal de Baños de Agua Santa.” - Jácome Caiza, Johny Patricio (2024)
Currently, the food industry focuses on providing consumers high-quality and contaminant-free food. The present study was carried out in Baños de Agua Santa City, specifically at the Slaughtering Center. The purpose of this research was the drawing up of a Good Manufacturing Practices (GMP) Manual to propose guidelines that define the management and handling of actions aimed at ensuring favorable conditions for the production of safe food. In the research, compliance with the GMP Standard was evaluated using a checklist based on resolution ARCSA--DE-067-2015-GGG. The results indicated a 60% compliance with the checklist, with 15% non-compliance and 25% not applicable. Additionally, visual verification means, documents, regulations, data collection, and spontaneous interviews with the personnel working at the facility were implemented, accompanied by descriptive researches to identify shortcomings found in the establishment. Finally, a Good Manufacturing Practices (GMP) Manual was developed, detailing the sanitation procedures and conditions (POE and POES). These results will serve as the basis for the development of a gradual improvement plan for Good Manufacturing Practices, and the proposal should be implemented gradually, ensuring an effective transition without interruptions in the daily operations of the Slaughtering Center.